1986
DOI: 10.1093/ageing/15.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence After Stroke: A Prospective Study

Abstract: During one year 151 patients with 154 strokes were studied prospectively to determine the occurrence and outcome of urinary incontinence after a stroke. Seventeen per cent had pre-existing urinary incontinence. At 1, 4 and 12 weeks, 60%, 42% and 29% of the survivors, respectively, were not continent. Cystometry was performed in those with moderate or severe urinary incontinence persisting 4 weeks after the stroke. Detrusor instability was present in 85% of those who had been continent prior to their stroke. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
3
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(43 citation statements)
references
References 0 publications
3
35
3
2
Order By: Relevance
“…A partial explanation may lie in shared risk factors for persistent UI; studies show that similar mobility difficulty and impaired function are primary associations rather than stroke-specific factors. 2,[31][32][33][34] In fact, urodynamic studies in incontinent stroke survivors show a similar diagnostic profile to that of incontinent patients without stroke, 32 with detrusor dysfunction predominating. 33 The few data available on anorectal function after stroke suggests that likewise there may be no specific pathophysiology underlying FI in stroke survivors.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A partial explanation may lie in shared risk factors for persistent UI; studies show that similar mobility difficulty and impaired function are primary associations rather than stroke-specific factors. 2,[31][32][33][34] In fact, urodynamic studies in incontinent stroke survivors show a similar diagnostic profile to that of incontinent patients without stroke, 32 with detrusor dysfunction predominating. 33 The few data available on anorectal function after stroke suggests that likewise there may be no specific pathophysiology underlying FI in stroke survivors.…”
Section: Discussionmentioning
confidence: 84%
“…2,[31][32][33][34] In fact, urodynamic studies in incontinent stroke survivors show a similar diagnostic profile to that of incontinent patients without stroke, 32 with detrusor dysfunction predominating. 33 The few data available on anorectal function after stroke suggests that likewise there may be no specific pathophysiology underlying FI in stroke survivors. 24 The prevalence is not dissimilar either; new-onset UI affects 40% of patients immediately after stroke, with 19% still incontinent at 3 months and 15% at 2 years.…”
Section: Discussionmentioning
confidence: 84%
“…27 Brocklehurst et al 27 found in their study that 6 additional survivors at a 3-year follow-up became incontinent of urine, 4 of whom subsequently died. Only 1 37 of 12 reports that specifically sought a link between stroke or brain injury and incontinence investigated the prevalence of premorbid incontinence. 4 -6,27,33,35,38 -42 This article suggests that 17% of 151 stroke survivors may have had incontinence before their stroke.…”
Section: Onset Of Incontinence In Stroke Survivorsmentioning
confidence: 99%
“…4 -6,27,33,35,38 -42 This article suggests that 17% of 151 stroke survivors may have had incontinence before their stroke. 37 The presence of premorbid incontinence is clearly important because it affects the apparent prevalence of incontinence due to stroke and because survivors who have premorbid incontinence may be very different from those who become incontinent after the stroke, with different morbidity and mortality. The rela- tionship between stroke and incontinence may not only be in one direction.…”
Section: Onset Of Incontinence In Stroke Survivorsmentioning
confidence: 99%
See 1 more Smart Citation